Adjuvant therapy of biliary tract cancers - Joanna Kefas; John Bridgewater; Arndt Vogel; Alexander Stein; John Primrose (Therapeutic Advances in Medical Oncology, 2023)
Biliary tract cancers (BTCs) are rare and heterogeneous malignant tumours including cholangiocarcinoma and gallbladder cancer. They are very aggressive, often refractory to chemotherapy and associated with an overall poor prognosis. Surgical resection remains the only potentially curative treatment option but less than 35% present with resectable disease. Adjuvant treatments have been widely used but until recently, supportive data were limited to non-randomised, non-controlled retrospective studies. Recent evidence from the BILCAP trial has established adjuvant capecitabine as the standard of care. But there are still unanswered questions as to the role of adjuvant therapy. Further prospective data and translational research with reproducible evidence of clinical benefit are needed. In this review of adjuvant therapy in resectable BTCs, we will summarise the latest evidence setting current treatment standards and highlight future prospects.